Impact of probiotic Lacticaseibacillus paracasei Strain Shirota (LcS) on aflatoxin exposure among healthy Malaysian adults: a randomized, double-blind, placebo-controlled intervention study - Chang, Wei Lin; Akiyama, Takuya; Wang, Jia-Sheng; Yong, Heng Yaw; Hassan, Faezah; Abu Saad, Hazizi; Jamaluddin, Rosita; Sabran, Mohd Redzwan (Elsevier B.V., 2025)
Background: Limited evidence suggests that probiotic Lacticaseibacillus paracasei strain Shirota (LcS) may reduce aflatoxin exposure in Malaysians, though individual factors influencing aflatoxin exposure remain unclear. Objectives: This study evaluated the effect of LcS on aflatoxin biomarker concentrations over a 12-wk intervention among healthy Malaysian adults. A secondary objective was to explore the individual factors associated with aflatoxin exposure using baseline data. Methods: A randomized, double-blind, placebo-controlled intervention involved healthy Malaysian adults (aged 20–60) of Chinese, Malay, or Indian ethnicities with elevated urinary aflatoxin M1 (AFM1) and serum aflatoxin B1 (AFB1)-albumin concentrations. Hundred and seventy-four (n = 174) subjects were randomly and equally assigned (n = 87/group) to consume either fermented milk with LcS (probiotic) (3 × 1010 CFU/80 mL/bottle) or milk without LcS (placebo) twice/d for 12 wk, with a 4-wk follow-up. Baseline data included sociodemographic characteristics, knowledge, attitude, and practice related to aflatoxin contamination, dietary intake, body weight, and physical activity status. Urine and fasting blood samples were collected every 2 and 4 wk for AFM1 and AFB1-lysine adduct analyses, respectively. Results: Eighty-five (n = 85) and 82 (n = 82) subjects in the probiotic and placebo groups completed the intervention, respectively. After adjusting for covariates, a significant effect was observed at postintervention in the probiotic group with a 23% reduction in urinary AFM1 concentrations compared with the placebo group (B = –0.26; Exp(B) = 0.77; P = 0.04). Serum AFB1-lysine adduct concentrations remained lower in the probiotic group throughout the study. Both aflatoxin biomarkers significantly differed by ethnicity (AFM1: P = 0.001; AFB1: P = 0.01). Subjects with lower aflatoxin knowledge had significantly higher AFB1-lysine concentrations (mean rank = 95.99) than those with higher knowledge (mean rank = 73.57) (P = 0.04). Urinary AFM1 concentrations were higher with cereal intake (ρ = 0.17, P = 0.03) but lower with protein intake (ρ = –0.18, P = 0.02). Conclusions: Ethnicity, knowledge level, and dietary intake influenced aflatoxin exposure. The benefits of consuming LcS to reduce aflatoxin exposure deserve further attention. Trial registration number: This trial is registered in the National Medical Research Register (NMRR-16-2693-3230) and clinicaltrials.gov (NCT03882294).